2021
DOI: 10.1002/htj.22172
|View full text |Cite
|
Sign up to set email alerts
|

Analytical study of heat and mass transfer effects on unsteady Casson fluid flow over an oscillating plate with thermal and solutal boundary conditions

Abstract: In this study, the impacts of heat and mass transfer characteristics on an isotropic incompressible Casson fluid flow over an oscillatory plate with the incidences of solutal and thermal boundary conditions have been investigated. Exact solutions of the fundamental equations governing the fluid flow are determined by using the Laplace transform technique. Numerical results based on analytical solutions are presented in graphical and tabular illustrations to clarify the behaviors of the fluid. Most interestingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…From the boundary conditions for the fluid flow described as follows 1,2,7,8 ]leftutrue¯=0, Ttrue¯=trueT¯, Ctrue¯=trueC¯ for ttrue¯0 and ytrue¯0,utrue¯=u0exp(αtrue¯ttrue¯), at ytrue¯=0 for ttrue¯0,Ttrue¯=trueT¯+(trueT¯wtrueT¯)u02ttrue¯v atytrue¯=0 for ttrue¯>0,Ctrue¯=trueC¯+(trueC¯wtrueC¯)u02ttrue¯v at ytrue¯=0 for ttrue¯>0,utrue¯0, Ttrue¯trueT¯, Ctrue¯trueC¯ as ytrue¯ for ttrue¯>0.…”
Section: Mathematical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…From the boundary conditions for the fluid flow described as follows 1,2,7,8 ]leftutrue¯=0, Ttrue¯=trueT¯, Ctrue¯=trueC¯ for ttrue¯0 and ytrue¯0,utrue¯=u0exp(αtrue¯ttrue¯), at ytrue¯=0 for ttrue¯0,Ttrue¯=trueT¯+(trueT¯wtrueT¯)u02ttrue¯v atytrue¯=0 for ttrue¯>0,Ctrue¯=trueC¯+(trueC¯wtrueC¯)u02ttrue¯v at ytrue¯=0 for ttrue¯>0,utrue¯0, Ttrue¯trueT¯, Ctrue¯trueC¯ as ytrue¯ for ttrue¯>0.…”
Section: Mathematical Analysismentioning
confidence: 99%
“…Also, it is identified that human blood, jelly, honey, concentrated fruit juices, soup, and tomato sauce are illustrations of the Casson liquid model. [1][2][3][4][5][6][7][8][9] Heat and mass transfer with boundary layer stream across an accelerating surface/plate is a basic field of fluid dynamics with several application areas. Vertical plates/surfaces appear in wrapping dynamics, surface texture, spray coating, biological sterilization, electro-microfluidics, thermoplastic stretching, and other applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patel 14 explored the impact of temperature generating thermal radiation in addition to Hall impacts on MHDs Casson liquid movement over a fluctuating plate into an absorbent medium. Endalew 15 analytically studied the temperature as well as accumulation transportations effects on unsteady Casson liquid flows past a fluctuating plate by the thermally as well as solutal frontier circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…In this research work, they have investigated important aspects of heat and mass transfer effects on MHD flow past through a porous medium. Recently, an analytical study of heat and mass transfer effects on a transient Casson fluid flow across an inclined plate is examined by Endalew [15].…”
Section: Introductionmentioning
confidence: 99%